Sunnyside - Come By Chance impact. Part 2. - Memorial University of Newfoundland. Extension Service
Open forum and panel discussion on the effects of oil on the area (part 2). Topics covered include the timing of production, job creation, training, interference with the fishery, oil spills, education, population growth, and where to obtain information